Unraveling a Rare Polygonal Gold–Pyrite Assemblage: Insights from the Lena Province, Bodaibo Mining District (Russia) - Isabella Pignatelli; Gaston Giuliani; Christophe Morlot; Louis-Dominique Bayle (Crystals)
A rare polygonal gold assemblage from the Bodaibo mining district (Russia) was analyzed in this study. It resembles cubic native gold from the same area described as a gold pseudomorph after pyrite. The polygonal assemblage differs from these cubic gold samples by the absence of striations, its stepped morphology, and the presence of euhedral pyrite. It was analyzed with non-destructive techniques (SEM, VSI, and X-ray CT) in order to preserve the integrity of this exceptional sample. The experimental data allowed us to understand how this rare sample could be formed. A formation of secondary deposits, i.e., eluvial placers, is compatible with the mobilization and precipitation of gold by surface effects on primary pyrite, as well as oxidation episodes producing iron oxides/hydroxides. The redox condition in the geological environment caused the pyrite dissolution and release of gold in its structure, leading to the formation of a thin layer of gold on pyrite by epitaxy rather than pseudomorphism.